Blood colony - Due, Tananarive, 1966- (Washington Square Press, 2009)
There's a new drug on the street: Glow. Said to heal almost any illness, its main ingredient is blood--the blood of immortals. A small but powerful underground railroad of immortals is distributing the blood, slowly wiping out the AIDS epidemic. But the Glow peddlers are being murdered by a violent, hundred-year-old sect with ties to the Vatican. And the only immortal born with the Living Blood is being hunted to fulfill an ancient blood prophecy that could lead to countless deaths.